Analisis Ketepatan Istilah Keuangan Dalam Laporan Akuntansi Ditinjau Dari Kaidah Bahasa Indonesia - Delima Sianipar; Natasya Ramadhani Citra; Kanaia Caisar; Dian Fitriani; Anisa Putri Lubis; Nurul Azizah (Jurnal Pustaka Cendekia Pendidikan, 2025)
This study reviews the evaluation of the accuracy of economic terms found in accounting reports based on Indonesian language rules. Financial reports play a crucial role as a means of conveying company financial information to various interested parties. Therefore, the choice of language that is clear, precise, and in accordance with the rules greatly affects the quality and readability of these reports. The method used in this study is qualitative with a literature review approach. Data sources were obtained from various relevant primary and secondary sources, including indexed scientific articles, research reports, and relevant textbooks. The findings show that language errors, such as the use of incorrect terms or inaccurate translations, can reduce the comprehensibility, credibility, and accuracy of financial reports. Conversely, the use of consistent, standard, and communicative language can increase transparency and trust among interested parties. Therefore, linguistic accuracy is an important element in maintaining the quality of accounting reports, as well as demonstrating the need for standardization of terms and ongoing training for financial report preparers.